Association Rules in Innovative Technology Collaboration - (:unkn) unknown (IEEE, 2015)
SMEs are motivated to collaborate for research and innovation in order to survive in global competition. Recent studies showed that using advanced communication and information technologies will improve innovative collaboration among the SMEs. In competitive environment, technology based SMEs need to constitute successful collaborations for sustainability. Randomly chosen collaborators have shown failures that caused the fear to become an obstacle. Failures are mainly faced by the lack of innovation culture and the wrong collaboration type. Technoparks are the main field of research of high technology business catalyzing the innovation. Different units in technoparks may emerge perceptible competences, and productive businesses. Most effective players of regional innovation are innovation stimulating institutions. This study aims to define and validate the association rules for success for collaborations in the techno parks. A survey is run on more than 110 SMEs in 4 techno parks of Turkey. Statistical analysis and machine learning methods are applied to define the association rules for success. Rules achieved by applying the logistic regression are cross validated with the rules detected by applying support vector machine. The validated collaboration rules extracted as a result of the study will support strategic decisions for innovative technology collaboration.
Keywords: RESEARCH-AND-DEVELOPMENT; SME COLLABORATION; NETWORKS